Sweet Syndrome secondary to infection: A case report (Bangladesh Journal of Medical Science, 2022)
We present a case of a patient with Sweet Syndrome secondary to possible bacterial infection. The diagnosis of Sweet Syndrome was made based on his clinical and histopathological findings. Sweet syndrome is a rare inflammatory disorder characterised by tender erythematous skin lesions, often accompanied with fever, neutrophilia and leukocytosis. It is generally classified into classical (or idiopathic), drug-induced or malignancy-associated, each of which has its own features.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 922-925